Head‐to‐head comparison between plasma ptau‐217 and Flortaucipir‐PET in amyloid‐positive patients with cognitive impairment. (20th December 2022) - Mundada, Nidhi S.; Thijssen, Elisabeth H; Iaccarino, Leonardo; Okoye, Obiora C; Shankar, Ranjani; Soleimani‐Meigooni, David N.; VandeVrede, Lawren; Lago, Argentina Lario; Miller, Bruce L.; Teunissen, Charlotte E.; Rojas, Julio C.; Dage, Jeffrey L; et al.
Abstract: Background: Plasma measurements of phosphorylated tau (ptau) have emerged as promising biomarkers for Alzheimer's disease (AD). Studies have shown strong associations between ptau and tau‐PET that are mainly driven by the difference between amyloid‐positive and amyloid‐negative patients. However, the relationship between ptau and tau‐PET is not well characterized within patients with AD. We conducted a head‐to‐head comparison between plasma ptau‐217 and tau‐PET in patients at the clinical stage of AD and assessed biomarker relationships with demographic and clinical variables. Methods: Eighty‐seven amyloid‐positive patients (age=66±10, 48% women) with mild cognitive impairment (n=53) or dementia (n=34) underwent structural MRI, amyloid‐PET (11C‐PIB), tau‐PET (18F‐flortaucipir, FTP), Mini‐Mental State Examination (MMSE, with 28 patients having longitudinal measures 1.5±0.7 years after baseline) and blood draw within a year. Mean cortical PET‐Standardized Uptake Value Ratio (SUVR) were extracted using FreeSurfer5.3. Plasma ptau‐217 concentrations were measured using an electrochemiluminescence‐based assay on the Meso Scale Discovery platform. Results: Ptau‐217 and cortical FTP‐SUVR were strongly correlated (r=0.61, p<.001, Figure 1). Younger age and female sex, but not APOE4, were associated with higher ptau‐217 and FTP‐SUVR (Figure 2). Amyloid‐PET levels were mildly associated with FTP‐SUVR (r=0.26, p=0.02), not ptau‐217 (r=0.10, p=0.36, Figure 2). The relationship between ptau‐217 and cortical FTP‐SUVR was not modified by age, sex, APOE4, or PIB‐PET (interactions: p's>0.25). In the whole group, ptau‐217 was associated with FTP‐SUVR in temporo‐parietal and dorsal prefrontal cortices (Figure 3A). However, ptau‐217‐FTP association patterns varied with amyloid burden: in patients with moderate amyloid (<97.7 Centiloids), ptau‐217 was more strongly associated with temporal FTP‐SUVR whereas associations were stronger in primary cortices in patient with higher amyloid levels (Figure 3B). Cross‐sectionally, higher ptau‐217 and FTP‐SUVR were independently associated with lower MMSE (Table 1; Figure 4A). In separate mixed effect models, higher baseline ptau‐217 and FTP‐SUVR were associated with more severe longitudinal decline in MMSE (Figure 4B); when both biomarkers were entered in the same model, only FTP‐SUVR remained significant (Table 2). Conclusions: In amyloid‐PET‐positive patients with cognitive deficits, ptau‐217 and tau‐PET had comparable patterns of association with demographic and clinical variables. However, cross‐modal and clinical associations tended to be stronger for tau‐PET than ptau‐217.